Formulation of Betel Leaf (Piper Betle L.) Essential Oil Patch Buccal with Variation CMC-Na and Carbopol as Mucoadhesive Polimers - Amitia Nice Tiensi; Tri Ratna S.; T. N. Saifullah Sulaiman (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Betel leaf (Piper betle L.) contains essential oils that have antibacterial activity. The research aimed to determine the effect of CMC-Na and carbopol concentration as mucoadhesive polymers on the physical properties of bucal patches of betel leaf essential oil and inhibition activity of bacterial Streptococcus mutans. The essential oil was extracted by distillation on steam-water method, detection of compounds by GC-MS. Patches are made by the solvent casting method, with varying levels of polymer CMC-Na and carbopol, namely: formula I (80%: 20%), formula II (60%: 40%), formula III (50%: 50%), formula IV (40%: 60%), formula V (20%: 80%). The patchs were tested on their physical properties and antibacterial assay against streptococcus mutans. The results showed that the five formulas had uniform weight, thickness, folding endurance, good swelling index, and neutral pH. Higher levels of CMC-Na could increase the weight, thickness, folding endurance, swelling index, and antibacterial activity. Formula I provides higher antibacterial activity than other formulas.